The influence of psychological factors on breast milk production among breastfeeding mother - Lajuna, Lia; Sriyanti, Cut (Institute of Computer Science (IOCS), 2025)
Breast milk production is a physiological process strongly influenced by maternal psychological conditions such as stress, anxiety, emotional exhaustion, and sleep quality. Psychological disturbances have been shown to interfere with hormonal reflexes essential for lactation—particularly oxytocin and prolactin—thereby affecting both the smoothness and volume of milk production. This study employs a systematic review method to analyze scientific articles published between 2013 and 2024 in both Indonesian and English, focusing on the psychological factors affecting breastfeeding. Articles were sourced from Google Scholar and PubMed, screened using defined inclusion criteria, and analyzed descriptively. The findings indicate that most studies report a significant negative correlation between stress, anxiety, and breast milk production, especially during the early postpartum period. However, some studies report inconsistent results, likely due to moderating factors such as social support, prior breastfeeding experience, employment status, and maternal coping mechanisms. In addition, sleep quality, breastfeeding behavior, and physical comfort also contribute to breastfeeding success. These results highlight the need for a holistic approach in maternal health services, including psychosocial interventions, behavioral education, and support from family and workplaces, to address psychological barriers that hinder successful breastfeeding.